2005
DOI: 10.1093/humrep/deh739
|View full text |Cite
|
Sign up to set email alerts
|

Stress and outcome success in IVF: the role of self-reports and endocrine variables

Abstract: The significant positive association of adrenaline concentration with pregnancy and with depression suggested that this adrenal hormone could be one of the links in the complex relationship between psychosocial stress and outcome after IVF/ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
1
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 35 publications
6
74
1
9
Order By: Relevance
“…The remaining five studies failed to find any significant associations between cortisol and pregnancy outcomes (Lovely et al, 2003;Lewicka et al, 2003;Smeenk et al, 2005;Nouri et al, 2011;Csemiczky et al, 2000). These equivocal findings are in contrast to evidence from animal studies which have shown a more consistent relationship between elevated cortisol levels and impaired reproductive outcomes across a range of species (Dobson and Smith, 1995;Alejandro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining five studies failed to find any significant associations between cortisol and pregnancy outcomes (Lovely et al, 2003;Lewicka et al, 2003;Smeenk et al, 2005;Nouri et al, 2011;Csemiczky et al, 2000). These equivocal findings are in contrast to evidence from animal studies which have shown a more consistent relationship between elevated cortisol levels and impaired reproductive outcomes across a range of species (Dobson and Smith, 1995;Alejandro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…urine samples, mean ± = standard deviation cortisol levels for pregnant (222±121 μg/24 h.) and non-pregnant (215±131 μg/24 h.) women using assisted reproduction were similar although higher than levels for an egg donor group (171±40 μg/24 h.) [13]. Another study collected nocturnal urine and first morning voids across three IVF treatment cycle intervals; no significant differences were detected for cortisol in pregnant and non-pregnant women, but an inverse association was described for adrenaline [14]. In contrast, studies of couples conceiving unassisted reported inverse associations between pregnancy and psychological stress measured using salivary alpha-amylase as a biomarker, but not when using salivary cortisol [1,2].…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies employing psychometric measures, biological stress measures, or both have reported varied, and often conflicting, results for associations between psychological stress and IVF outcomes [5,13,14,[23][24][25][26]. Infertility, as well as its treatment, can be considered significant chronic stressors, but the neuroendocrine components of this response and the extent to which environmental contaminants modulate this are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown than stresssensitive hormones prolactin and cortisol are elevated in infertile women during IVF. 24,25 However, all these studies have compared the cortisol level during different phases of in vitro-fertilization treatment. Similary, Nepomnaschy et al measure urinary cortisol level and found that increased cortisol levels associated with a higher risk of early pregnancy loss 26 whereas Nelson measured total plasma cortisol level and found no relation to spontaneous abortion.…”
Section: Discussionmentioning
confidence: 99%